Search 72,463 tutors
FIND TUTORS
Ask a question

Answers by Sunil D.

Nisya, We can re-write the question as 1/(ax - b)1/2 - ((ax - b)1/2)/b and then perform subtraction using the LCM of b(ax-b)1/2. We then get the fraction (b - ax +b)/ (b(ax-b)1/2) or (2b - ax) / (b(ax-b)1/2). Hope this helps.    

Nat, Magnesium has the atomic number 12. There are 12 electrons in the outermost shell. Mg atom would look like  this Mg: (if we ignore the full shells). This molecule is very reactive, as it wants to reach a full shell, and it can do that by losing those two electrons. When magnesium...

Sometimes the answer is not well defined, like in this case. This problem may be solved by the quadratic method, like Kirill did, or by completing the square for y2 - y/x, by adding and subtracting 1/4x2. The problem then reduces to   (y2 - y/x + 1/4x2) -16 - 1/4x2 = 0, or (y...

Crystal, This problem is a variant on y = mx + c. You have P = 5.9t – 11,706, with y being P, m = 5.9, x = t and c = -11706.    To evaluate P for t = 1985 and 2000, substitute these values in the equation to get the values of P (in percent). The values are ~ 5 and 94.  ...

Erica,    One way to visualize the function is to assume values for x and see the values of y that are derived. The function is y2 = 3x2 -4x -8. For x = 0, y2 = -8. Here the answer is not a real number.  If x = 1, y2 = 3-4-8 = -9; again not a real number. If x...

x = 4, y = 12 (answer)

If y varies directly as x, then y must be a function of x, or y = a * x. Looking at the values of y (12) and x (4), and putting them in the equation y = ax, we get 12 =a*4 ,  or a = 3. hence y = 3x must be the the equation that relates x and y.

Using Henry's Law, we get the partial pressure of the gas above the solution as p = 0.2 (atm M-1)  * 0.1 (g) / 106.2 (g/mole) * 1/1 (L) , since total volume of liquid is 1L. This value of p is transferred to the gas equation PV = (g/M)RT to determine the weight g of xylene in the headspace...

The problem is x2 - 6x -27 = 0 The factors of this can be expressed as (x + a)*(x + b) = 0 There are two values of x because this is a quadratic equation. If the factors are expanded, we get the following:    x2 + (a + b)x + a*b = 0. Applying this into...